A NOVEL TOPICAL GEL OF THE FRESH YOUNG COCONUT HUSK ETHANOLIC EXTRACT DEDICATED FOR DIABETIC WOUND HEALING - NASTITI, CHRISTOFORI MARIA RATNA RINI; DWIATMAKA, YOHANES; PATRAMURTI, CHRISTINE; GANI, MICHAEL RAHARJA; RISWANTO, FLORENTINUS DIKA OCTA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to develop and to optimize the formulation of novel Fresh-Young Coconut-Husk-Ethanolic-Extract (FYCHEE) gels by Response Surface Methodology (RSM) of a Box Behnken Design (BBD), and to investigate the activity of novel FYCHEE topical gels on accelerating the Diabetic Wound Healing (DWH). Methods: The FYCHEE was prepared by maceration using 96% ethanol and was standardized. Gels were formed by incorporating the FYCHEE into the gel-forming system containing Diethylene-Glycol Monoethyl-Ether (DGME), Carbopol 940, and Triethanolamine (TEA). Sixteen experimental runs were set using BBD. Physical properties (viscosity, pH and spread ability) were further characterized. The data were analyzed and optimized using “rsm” package of the R software. The predicted model of DGME, Carbopol 940 and TEA composition was further validated. The in vivo study of the activity of FYCHEE gels on accelerating DWH was conducted on groups of male Wistar rats in 12 d of topical application of FYCHEE gels containing 5%, 10%, 20% extracts. Results: The FYCHEE gels performed light-brown semisolid texture with varied physical characteristics. The RSM generated visualization of response surface plots based on three model equations. The novel FYCHEE gels with optimum responses have been well developed (DGME: Carbopol 940: TEA = 8:0.8:0.6). The formulation based on predicted composition showed 1.194±0.136 Pa. s (viscosity), 5.715±0.213 (pH) and 4.997±0.265 cm (spread-ability). The FYCHEE gels showed significant results on accelerating the wound closure in 12 d, with percentage of (88.798±4.697) %, (91.685±3.124) %, and (93.060±1.687) % for FYCHEE of 5%, 10%, and 20%, respectively. These results were similar to the positive control (p>0.05). Conclusion: The novel FYCHEE gels were successfully fabricated with standardized FYCHEE. The RSM of the BBD was applied satisfactorily to optimize the formula. Further study of FYCHEE gels on accelerating DWH revealed promising results of the FYCHEE gels to be potentially developed as diabetic wound healing topical preparation.